2020
DOI: 10.1016/j.jtauto.2020.100047
|View full text |Cite
|
Sign up to set email alerts
|

Immunological mechanism of IgG4-related disease

Abstract: IgG4-related disease (IgG4-RD) is an immune-mediated inflammatory disorder in multiple organs, characterized by abundant infiltration of IgG4-positive plasmacytes and fibrosis in the involved organs. The precise pathogenic mechanism of IgG4-RD still remains unclear. Aberrant innate and adaptive immunity are considered as the main pathogenesis of IgG4-RD. Recent studies have shown that abnormal adaptive immune responses mediated by T helper type 2 ​cells, regulatory T lymphocytes, CD4 + c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 72 publications
0
37
0
1
Order By: Relevance
“…T follicular helper (Tfh) cells are a subset of CD4+T cells that are known to be involved in the differentiation and class switch of B cells during their development. Among Tfh cells subsets, Tfh2 cells could induce the differentiation of naïve B cells into plasmablasts, subsequently promoting the production of IgG4 in active ( 48 ). Glucocorticoid-induced remission in patients with IgG4-RD is associated with a decrease of circulating CD4+ CTLs, a recently identified potentially pathogenic population of T lymphocytes ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…T follicular helper (Tfh) cells are a subset of CD4+T cells that are known to be involved in the differentiation and class switch of B cells during their development. Among Tfh cells subsets, Tfh2 cells could induce the differentiation of naïve B cells into plasmablasts, subsequently promoting the production of IgG4 in active ( 48 ). Glucocorticoid-induced remission in patients with IgG4-RD is associated with a decrease of circulating CD4+ CTLs, a recently identified potentially pathogenic population of T lymphocytes ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, while ECD and IgG4-RD share some physiopathological characteristics, these diseases exhibit distinctive clinical features, suggesting they are distinct disorders. The increased production of IgG4 is frequently driven through a Th2 response to IL-4, IL-5, or Il-13 and by anti-inflammatory IL-10 and TGFβ cytokines 22 . Although ECD patients exhibit a Th1 immune response 4,6 , the present study suggested that while patients who carry the BRAF mutation exhibit higher circulating IL-10 concentrations and are more likely to exhibit high IgG4 levels than patients who lack the mutation, , suggesting that IL-10 might contribute to the IgG4 immune response in ECD.…”
Section: Discussionmentioning
confidence: 99%
“…BAFF promotes immunoglobulin class switching, whereas IL-13 maintains Th2-cell dominant immune responses ( 68 ) ( Figure 1 ). Thus, activated basophils may induce IgG4 production via TLR signaling ( 69 ) ( Table 1 ). The specific TLR ligands that activate basophils in IgG4-RD patients are unknown.…”
Section: Type 2 Immunity In Igg4-rdmentioning
confidence: 99%